Implementing Religious Moderation in Digital Age: Digital Literacy Strategies to Counter Radicalism in Educational Settings - Aryani Aryani; Aam Aminah; Afifah Ansori; Celvin Alami; Ani Yunita Santi; M. Makhrus Ali; Tri Hariyati; Khairunesa Isa (Universitas Nurul Jadid, 2025)
This study is motivated by the increasing use of digital technology in students’ lives, which not only provides easier access to information but also creates risks related to the spread of intolerant content, hate speech, and radical ideologies. In the context of primary education, schools have a strategic role in instilling the values of religious moderation from an early age through learning activities, habituation, and the strengthening of digital literacy. This study aims to describe the implementation of religious moderation in the digital era, analyze digital literacy strategies in countering radicalism, and identify the supporting and inhibiting factors in its implementation at SDN 6 Kelapa Tujuh Lampung Utara. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings show that religious moderation is implemented through the integration of tolerance, non-violence, national commitment, and mutual respect in Islamic Religious Education, Pancasila Education, literacy activities, and school culture. Digital literacy strategies are applied through education on healthy internet use, information filtering, strengthening digital ethics, and guidance from teachers and parents. This study concludes that digital literacy-based religious moderation serves as an important preventive strategy in shaping students who are religious, critical, tolerant, and less susceptible to radical narratives in digital spaces